KEGIATAN SOSIALISASI TUKANG KEGIATAN REHABILITASI RUMAH TIDAK LAYAK HUNI KECAMATAN BALARAJA KABUPATEN TANGERANG - Puro, Sarjono; Nurmawati, Bernadete; Maria, Kiki (LPPM Institut Pendidikan Nusantara Global, 2024)
The construction of the Gebrak Pakumis House is part of the commitment of the Tangerang Regency Government which is managed by the Tangerang Regency Housing and Settlement Service in the renovation program for uninhabitable houses belonging to poor residents. Balaraja District, Tangerang Regency, which borders directly with DKI Jakarta Province, is one of the many destinations for migrants outside the residential areas of residents who work around the area. Residential land is getting narrower day by day because most of the area is used as residential areas, causing slum settlements to form. The Uninhabitable House Rehabilitation Activity involves builders who will carry out house construction activities. The builders still have high hopes that this Uninhabitable House Rehabilitation Activity can fully assist in renovating uninhabitable houses into habitable houses that meet the requirements. Location of outreach activities Providing information to builders about the implementation of Rehabilitation construction for Uninhabitable Houses. Preparation method, coordination, identification and verification of residents' houses included in the list of potential aid recipients (CPB), making planning drawings, socializing craftsmen, discussions. In socialization activities, more time is needed because many craftsmen still have minimal understanding of construction, although some craftsmen already have quite a lot of experience. As a result of this socialization, craftsmen understand more about implementation drawings, which in previous activities relied on experience. With the results obtained from this socialization, craftsmen need technical guidance to increase the knowledge and competence of craftsmen to ensure the implementation of Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia Number 1 of 2023